Labour Regulation and Employment Patterns*. Issue 2 (May 2015) - Fenwick, Colin; Martinsson, Sara; Pignatti, Clemente; Rusconi, Giuditta
Abstract : Chapter 4 reviews changes in employment regulation in 63 countries over the past two decades, focusing on changes in the regulation of different forms of employment (in particular agency, fixed‐term, and part‐time work) and employment protection law (EPL). The most distinct changes, globally and especially in Europe, have been the increases in the relative strength of labour regulation that requires equal treatment for workers in agency, fixed‐term and part‐time work. Since the crisis, however, the relative strength of EPL fell in both developing countries and the EU. In the EU, decreases were driven largely by changes to notice periods for dismissal, and to the calculation of redundancy compensation. In the same period, on average, other advanced and emerging economies continued to slightly increase their overall level of EPL. The chapter also analyses the effects of labour regulation and changes in regulation on key labour market indicators including the unemployment rate, the labour force participation rate and the employment to population ratio. The analysis presented in the chapter highlights that there are no negative effects from increased labour regulation. This also confirms the findings of previous studies that showed there was no statistically significant effect between the strength of labour regulation and employment levels.